2021
DOI: 10.13004/kjnt.2021.17.e3
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Frontal Sinus Fractures Management: Experience from High-Trauma Centre

Abstract: Objective Analysis of our traumatic brain injury data, reviewing current literatures and assessing planning valuable decision making in frontal sinus fracture for young neurosurgeons. Methods Hospital data base for head trauma was retrieved after board permission for retrospective analysis of cases admitted from 2010–2020. Patients with frontal sinus fractures and head trauma were identified according to a flow chart. Variables of the study included patients' demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…A 2021 review of 338 cases in Israel reported an operative rate of 22.8%, 24 while a similar-sized review published in the same year in Egypt reported an operative rate of 46.1%. 25 In congruence with proposed frontal sinus management algorithms and other recent studies, 7,10,14,15,21,26 both fracture displacement and comminution were significantly associated with surgical intervention in our sample. Fractures were more likely to be operative with associated dural tears/CSF leaks and FSOT involvement.…”
Section: Discussion and Literature Reviewsupporting
confidence: 90%
“…A 2021 review of 338 cases in Israel reported an operative rate of 22.8%, 24 while a similar-sized review published in the same year in Egypt reported an operative rate of 46.1%. 25 In congruence with proposed frontal sinus management algorithms and other recent studies, 7,10,14,15,21,26 both fracture displacement and comminution were significantly associated with surgical intervention in our sample. Fractures were more likely to be operative with associated dural tears/CSF leaks and FSOT involvement.…”
Section: Discussion and Literature Reviewsupporting
confidence: 90%
“…Previous studies have demonstrated associations between facial fracture sites and associated head injury or TBI. Such associations have been reported for upper face fractures, mostly frontal sinus, 34,35 mandibular fractures, 36 and maxillary Le fort fractures 37 . A link between zygoma and orbital injuries and possible TBI was addressed herein.…”
Section: Discussionmentioning
confidence: 66%
“…10 Road traffic accidents were the common cause of frontal fractures in multiple studies and the percentages range from 52-75%. 8,9 The location and configuration of FSF determine the treatment type. It can be treated conservatively with medication prescriptions and follow-up, or surgically with cranialization, obliteration, or internal fixation only.…”
Section: Saudimentioning
confidence: 99%
“…There is a high tendency for frontal fractures to involve the male gender, according to studies from different places. Strong et al 8 and Al-Shami et al 9 found that men were involved in 89% and 84% of frontal fractures. Similarly, Johnson et al’s systematic review and meta-analysis showed that 84.1% of frontal fractures occurred in men.…”
mentioning
confidence: 99%
See 1 more Smart Citation